Bandwidth-immediacy-social connectedness framework for rural secondary school’s extended m-learning experience - Ain Arissa Zainuddin; Noris Mohd Norowi; Rahmita Wirza O. K. Rahmat; Mas Nida Md. Khambari (Intelektual Pustaka Media Utama, 2026)
Mobility, instant access to knowledge, social interaction, and flexibility in terms of time, location, and pace are just few of the many benefits that mobile learning (m-learning) provides. To build an ideal m-learning platform, a framework acts as a plan that directs the construction of a unified, user-friendly, and efficient m-learning environment. Through the utilisation of Stanford’s bandwidth-immediacy matrix as a foundational framework, the purpose of this study is to investigate the possibility of incorporating social connectedness as z-axis in between the bandwidth and immediacy axes by proposing a 3-dimensional matrix called bandwidth-immediacy-social connectedness in blue zone framework, shorten as BISC-B framework. A progressive web application (PWA) called bridging the urban-rural knowledge dissemination and learning gap (BURDLe) was developed with the implementation of BISC-B in order to fulfil the objectives of this study. BURDLe was evaluated for 2 weeks by students and teachers from Bachok, Kelantan, a remote Malaysian district. This study collected data sequentially using explanatory methods. Quantitative and descriptive analysis were used to summarise questionnaire data. Conversely, interviews were qualitatively analysed to validate the questionnaire results. The result of this study has revealed that social-connectedness is a factor that can influence the m-learning experience, along with bandwidth utilisation and immediacy.